Undrained cyclic response of a dense saturated sand with various grain sizes and contents of nonplastic fines: Experimental analysis and constitutive modeling. Issue 145 (June 2021) - Xu, Ling-Yu; Cai, Fei; Chen, Wei-Yun; Zhang, Jing-Zhe; Pan, Dong-Dong; Wu, Qi; Chen, Guo-Xing
Abstract: The densification can increase the liquefaction resistance of sands. However, in most engineering practice, sands are not pure and contain a significant amount of fines with particle diameter smaller than 0.075 mm. Thus, it is necessary to quantitatively evaluate the influence of fines on the undrained cyclic behavior of dense sandy soils. In this study, a series of undrained cyclic triaxial tests were conducted on the dense saturated sand with various mean grain sizes and contents of nonplastic fines. A unified constitutive framework is modified to improve the capability of simulating the cyclic mobility behavior of sandy soils. The results indicate that the effect of the mean grain size on the cyclic stress ratio required to cause 5% double-amplitude axial strain for sandy soils depends on the amount of nonplastic fines added. Moreover, a good correlation between the cyclic resistance ratio and the initial value of the equivalent granular state parameter is obtained for various fines contents and mean grain sizes of nonplastic fines. The influence of the fines content and mean grain size of nonplastic fines on the liquefaction resistance of sandy soils can be reasonably characterized by the constitutive framework using a set of unique parameters. Additionally, the capability of the constitutive framework for describing the influence of the fines content on the cyclic instability behavior of sandy soils is also evaluated against the experimental data in the literature. Highlights: Effects of FC and d 50 f on the undrained cyclic behavior of dense sandy soils are experimentally investigated. A good correlation between CRR 15 and ψ 0 * is obtained for various FC s and d 50 f s. 30 undrained cyclic triaxial test results are simulated by a set of unique model parameters. The cyclic mobility behavior of sandy soils is reproduced by a modified unified constitutive framework.